Investigating the use of speaking strategies in the performance of two communicative tasks: The importance of communicative goal - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2018)
Although the ability to speak is usually seen as a key manifestation of learners’ ability in the target language they are attempting to master, research has not given ample attention to strategies that can be employed to enhance this skill. In fact, the bulk of such empirical investigations has mainly focused on communication strategies that are reactive devices, predominantly used to overcome difficulties in successful conveyance of meanings and messages, and even this line of inquiry has been neglected in recent years. The study reported in this paper aims to partially bridge this gap by examining the speaking strategies that advanced learners of English used in the performance of two communicative tasks, differing in the extent to which the participants were required to make a contribution to their successful completion. The data collected by means of open-ended questionnaires that were administered immediately after the completion of the two tasks yielded crucial insights into the nature of the speaking strategies and the ways in which the communicative goals inherent in task type influenced the choice of speaking strategies.